Calidad de vida del adulto mayor: efectos del programa estilos de vida para un envejecimiento activo - essalud. distrito la esperanza, provincia de trujillo, en el año 2014. - Lozada Oliva, Johana Rosa Noelia (2015)
This research is descriptive, which aims to demonstrate the effect of lifestyle program for active aging in the quality of life of older adults Older Adult Centre La Esperanza. It was found that 48.3% of elderly practicing relaxation techniques to cope with stress, which has encouraged them to be loosened meet any liabilities assumed in their homes or jobs they perform, not allowing them time to get distracted. We worked with 60 seniors of the Elderly La Esperanza-Essalud Center, with the aim of determining the effect of the program of lifestyle for active aging in the quality of life of older adults in physical, social and psychological aspects. In which ethnographic methods, inductive-deductive, statistical; the life history techniques, survey and interview, using questionnaire instruments and recording the interview were actually allowed to take the results for this research. From the results such as that 65% of older adults they consider that currently enjoy good physical health, starting with the care and responsibility of their welfare incentive from the program, allowing them to better adapt to the changes they are presenting in this process. In addition to participating in this social space they can share experiences and experiences with their peers and perceived worth. However it also has 23% of participants who value regulate their health, considering that having controlled their disease, they still feel vulnerable to fully enjoy what they previously performed, which worsens when seen difficulties at home and them uneasy. Program lifestyles for active aging affects the quality of life of the elderly in the psychological to achieve the gradual management and control through education workshop emotional aspect. The presence of feelings of sadness when they invade the nostalgia or feelings of frustration is overcome when changing activities, feel serene and taken away to reflect in search of the solution. But the answer depends on what they have learned during certain painful situations or coping mechanisms of emotions from feeling excited (33.3%) to be afraid that things do not turn them well (45.7%).